TGFB1 polymorphisms and TGF‐β1 plasma levels identify gastric adenocarcinoma patients with lower survival rate and disseminated disease. Issue 2 (4th December 2020) - Juarez, Ignacio; Gutierrez, Alberto; Vaquero‐Yuste, Christian; Molanes‐López, Elisa M.; López, Adela; Lasa, Inmaculada; Gómez, Remedios; Martin‐Villa, José Manuel
Abstract: TGF‐β1 is involved in tumour growth. Four TGFB1 SNPs and TGF‐β1 production by stimulated PBMC were determined in seventy‐eight gastric adenocarcinoma patients. In addition, TGF‐β1 levels were measured in the plasma of further thirty patients. rs1800471‐G/C genotype was prevalent in patients (20.7%) compared to controls (8.4%), as it also was the rs1800468 SNP‐G/A genotype in stage IV patients (20.7%) compared to stage I, II and III patients, combined (10.3%). Conversely, the T/T rs1800469 SNP‐T/T genotype was absent in the former group and present in 19.0% in the latter. Furthermore, the rs1800469‐C/rs1800470‐T (CT) haplotype was found in 15.0% of stage IV patients as compared to 3.0% of the remaining patients (3.0%) and also identifies patients with worse five‐year life expectancy ( P  = .03). TGF‐β1 synthesis by stimulated PBMCs was significantly lower in patients with the risk SNPs or haplotype, compared to the alternative genotype. Finally, TGF‐β1 plasma levels were lower in patients with worse life expectancy. Analysis of TGFB1 SNPs and measurement of plasma TGF‐β1 levels serves to identify patients at risk of developing a more aggressive disease.